Injury characteristics in Norwegian male professional football: A comparison between a regular season and a season in the pandemic - Dalen-Lorentsen, T.; Andersen, T. E.; Thorbjørnsen, C.; Brown, M.; Tovi, D.; Braastad, A.; Lindinger, T. G.; Williams, C.; Moen, E.; Clarsen, B.; Bjørneboe, J. (Frontiers in Sports and Active Living, 2022)
The CoronavirusDisease-19 (COVID-19) pandemic forced the Norwegian male premier league football season to reschedule, reducing the fixture calendar substantially. Previous research has shown that a congested match schedule can affect injury rates in professional football. Therefore, we aimed to investigate whether the Norwegian premier league teams suffered more injuries in the match congested 2020 season than the regular 2019-season. We invited all teams having participated in both seasons to export their injury data. Only teams that used the same medical staff to register injuries in both seasons were included, and to maximise data comparability between seasons, we applied a time-loss injury definition only. Eight of 13 teams agreed to participate and exported their injury data. The 2020 season was 57 days shorter than the 2019 season. The match injury incidence differed insignificantly (incidence rate ratio 0.76 (0.48 to 1.20; p=0.24) in the 2020 season compared to the 2019 season. Furthermore, we found no differences in the number of injuries, days lost to injury, matches missed to injury, or injury severity. We present the first injury data from a complete post-lockdown professional football season. We could not detect any differences between the two seasons, suggesting the congested match calendar in the 2020 season is a safe alternative in future seasons.